CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI WUJUD KONKRIT KEPEDULIAN PERUSAHAAN - Melita, Yerah (Jurnal Insani, 2015)
Companies that do not do corporate social responsibility (CSR) activities, in addition to sanctions, can also be considered selfish and do not want to know the interests of others, the environment and communities. Conversely, companies that implement their CSR programs have a notice, caring and responsible, in particular social responsibility for other people, the environment and communities.Through CSR activities, the company will be better known, appreciated, and supported by the public so that CSR activities are activities that are beneficial to the company and the parties concerned. CSR activities are also a concrete manifestation of corporate concern.